Towards an authentication service for Peer-to-Peer based Massively Multiuser Virtual Environments. (29th December 2008) - Wacker, Arno; Schiele, Gregor; Schuster, Sebastian; Weis, Torben
In this paper we propose a distributed authentication service for Peer-to-Peer (P2P) based massively multiuser virtual environments. Such a service is necessary to provide security, e.g., preventing a user's account being stolen or the user being impersonated. We describe two variants of our authentication service. The first uses certificates and a central certification authority to ensure the validity of user-generated public keys. These keys are then used to sign messages sent by the users' peers. The second variant distributes the users' public keys in the P2P network and uses quorums to verify them.